Screening anti-cancer compounds from rice industrial wastes - Ahmad Raus, Raha; Muhammad, Mohd Hafizul; Jamal, Parveen (IIUM Press, 2011)

(untitled)
In this study. anll-tumor promoting activity against breast cancer cells (MCF7) of riec industrial wastes crude extract was investigated. Methanol and warer extracts of the industrial wastes were tested using MTT assay. The most active extract for inhibition of the prolifer.llion ofbrcast cancer cell was aqueous extract of rice mixture wastes. All of the other industrial waste extracts also sho,",'ed anti-<;;ancer activity however. at lower level. With respe<:t to these results. rice mixture ,",'lIStes could be studied funher for their potentJalto treat breasl eanen cells.